Epipactis krymmontana (Orchidaceae), a new species endemic to the Crimean Mountains and notes on the related taxa in the Crimea and bordering Russian Caucasus - Fateryga, Alexander V.; Kreutz, Karel C.a.j.; Fateryga, Valentina V.; Efimov, Petr G. (Phytotaxa, 2014)
A new obligately self-pollinating species, Epipactis krymmontana, is described from the Crimea. The species is closely related to E. condensata from which it differs by its relatively loose and usually much shorter inflorescence, relatively elongate ovaries, much paler epichile with less protruding bosses and absence of a viscidium. It grows in beech forests, often mixed with oak and hornbeam, on calcareous soils. The new species was previously misidentified in the Crimea as E. purpurata or sometimes as E. condensata, the latter growing in hot, sunny places with sparse vegetation. The presence of typical E. condensata in the Crimea is considered doubtful, but it is undoubtedly present in the Russian Caucasus along with E. condensata subsp. kuenkeleana, which is a new combination proposed in place of E. purpurata subsp. kuenkeleana. Epipactis purpurata should be excluded both from the floras of the Crimea and the Russian Caucasus. An updated key to the species of Epipactis sect. Epipactis in the Crimea and Russian Caucasus is provided.